Early Life Origins of Health and Disease - Wintour-Coghlan, E. Marelyn; Owens, Julie (Advances in Experimental Medicine and Biology,, 2006)
Early Life Origins of Health and Disease is a new book which presents and discusses the many factors that may have impact on normal development. In a concise and readable manner, the authors consider both the proven and suggestive evidence that the high prevalence of hypertension, diabetes, obesity and, in some populations, kidney disease, may not be all due to genetics or adult environment alone. There is good evidence that stress and more subtle dietary deficiencies, as well as placental malfunction, may increase the risk that the offspring will develop these problems in later life. Finally, new and emerging evidence for other areas of human health and disease such a motor control and mental health is critically reviewed for the first time. The book is a 'must' for all scientists interested in researching these areas, as there is a critical evaluation of the methodology used and suggestions for the 'optimal' way in which to investigate these phenomena.